Comparative evaluation of antimicrobials for textile applications - Windler, Lena; Height, Murray; Nowack, Bernd (Environment international, 2013)
Many antimicrobial technologies are available for textiles. They may be used in many different textile applications to prevent the growth of microorganisms. Due to the biological activity of the antimicrobial compounds, the assessment of the safety of these substances is an ongoing subject of research and regulatory scrutiny. This review aims to give an overview on the main compounds used today for antimicrobial textile functionalization. Based on an evaluation of scientific publications, market data as well as regulatory documents, the potential effects of antimicrobials on the environment and on human health were considered and also life cycle perspectives were taken into account. The characteristics of each compound were summarized according to technical, environmental and human health criteria. Triclosan, silane quaternary ammonium compounds, zinc pyrithione and silver-based compounds are the main antimicrobials used in textiles. The synthetic organic compounds dominate the antimicrobials market on a weight basis. On the technical side the application rates of the antimicrobials used to functionalize a textile product are an important parameter with treatments requiring lower dosage rates offering clear benefits in terms of less active substance required to achieve the functionality. The durability of the antimicrobial treatment has a strong influence on the potential for release and subsequent environmental effects. In terms of environmental criteria, all compounds were rated similarly in effective removal in wastewater treatment processes. The extent of published information about environmental behavior for each compound varies, limiting the possibility for an in-depth comparison of all textile-relevant parameters across the antimicrobials. Nevertheless the comparative evaluation showed that each antimicrobial technology has specific risks and benefits that should be taken into account in evaluating the suitability of different antimicrobial products. The results also indicated that nanoscale silver and silver salts that achieve functionality with very low application rates offer clear potential benefits for textile use. The regular care of textiles consumes lots of resources (e.g. water, energy, chemicals) and antimicrobial treatments can play a role in reducing the frequency and/or intensity of laundering which can give potential for significant resource savings and associated impact on the environment. [Display omitted] ► We review textile antimicrobials by technical, environmental and health criteria. ► Synthetic organic compounds are used in significantly higher volumes than silver. ► Antimicrobial application rates are important determinants for resource efficiency. ► Each antimicrobial compound has specific pros and cons which must be considered.